New Latin American Communicology and Decolonial Giro. Continuities and ruptures - Sierra-Caballero, Francisco; Maldonado, Claudio; del Valle, Carlos (CIC. Cuadernos de Información y Comunicación, 2020)
The present article proposes to advance in the configuration of a new Latin American Communicology from the survey of the critical theory of social mediation, the encounter with the emancipatory and antagonistic academic culture of the Latin American School of Communication (ELACOM) and the fundamentals offered by the Decolonial Giro to rethink the Political Economy of Knowledge. The bet on the decoloniality of knowledge-informative power poses the challenge of reformulating the bases of the dominant paradigm of communicational science by means of a "dialogue of knowledge" with the cultural and epistemic matrices that today emerge from the Amerindian paradigm.
Keywords: Latin American communicology; ELACOM; Giro Decolonial; Political Economy of Knowledge; Amerindian Paradigm